Practice makes perfect? Association between students’ performance measures in an advanced dental simulation course - Baechle, Mary A.; Gottlieb, Riki; Carrico, Caroline K.; Brody, Erica R. (Journal of dental education, 2022)
Purpose This study examines the relationship between student performance measures during practice and exams using advanced dental simulation. Methods Data from 11 classes of first‐year dental students were extracted from Advanced Simulation software (DentSim™) related to Class I and Class II preparations including: total number of practice sessions, average practice score, exam scores, average time preparing teeth during practice/exam, and average time self‐evaluating preparations during practice/exam. Comparisons of average practice and exam scores were examined using paired t‐test. Relationships between practice/exam measures and exam scores were determined with multiple linear regression. Results Practice mean and exam scores were significantly associated; exam scores were significantly higher in both procedures. Class I: a significant positive relationship exists between both practice and exam measures: The average practice score was significantly associated with exam score (p < 0.001); time spent preparing the exam tooth was negatively associated with the exam score (p < 0.001); conversely, time spent self‐evaluating the exam tooth was significantly associated with an increase in exam score (p = 0.0135). Class II: exam score was significantly associated with two practice measures but neither of the exam measures: exam score for Class II mesioocclusal preparation was significantly associated with average practice score (p < 0.001) and the number of practice attempts (p = 0.025). Conclusion This study emphasizes the predictive value of novice learners’ deliberate, repetitive practice using advanced dental simulation, which enhances self‐assessment in early stages of psychomotor skill development. Future studies are needed to demonstrate the translation of these skills into a patient care setting.